Exercise heart rates determined by a ventilatory threshold vs. standardized equation methods in individuals with metabolic syndrome - Ruojiang Liu; Jinmei Qin; Feng Wang; Weizhen Xue; Huihui Zhu (Scientific Reports)
Abstract This study aimed to compare the target heart rate (THR) for aerobic exercise based on standardized physiological maximum value percentages with the first-ventilatory-threshold heart rate (HRVT1) in individuals with metabolic syndrome. Three HRmax prediction equations were used to calculate the THR as 35%, 40% and 45% of the heart rate reserve (HRR) and 55%, 60% and 65% of the HRmax, and the results were compared with the HRVT1. The HRVT1 was measured through a CPET that complied with current guidelines and laboratory standards. In addition, the THRs calculated by combining the HRmax-measured values with standardized methods were compared with those of HRVT1 as a supplement for situations where HRmax-measured values can be evaluated but gas exchange analysis cannot be performed. According to the Fox equation, the difference between the HRVT1 and 35% HRR was not statistically significant (t = − 0.528, P = 0.600). Bland‒Altman analysis indicated that the mean difference between the two values was − 0.350, which was close to the 0th line (SD: ± 4.595; 95% CI − 1.684–0.984), with 95% limits of agreement ranging from − 9.356 to 8.656; the interclass correlation coefficient (ICC) was 0.862 (P < 0.001, 95% CI 0.766–0.920), indicating high reliability. Regarding the results, the measured values indicate that 40% HRR and 70% HRPeak showed good reliability with HRVT1 (ICC: 0.850, 95% CI 0.747–0.913; and ICC: 0.719, 95% CI 0.551–0.832, respectively). Among Chinese patients with MetS, the THR calculated by combining the standardized 35% HRR method with the Fox equation shows excellent agreement with the HRVT1 obtained from the CPET. When the HRPeak can be obtained, the THR calculated from the 40% HRR and 70% HRPeak can better estimate the HRVT1. The above results can be used to guide patients to gradually start exercise training near the VT1 in cases where CPET data cannot be obtained.